PENGARUH MEDIA PEMBELAJARAN TEKA TEKI SILANG TERHADAP MOTIVASI BELAJAR SISWA KELAS V SDN 105273 HELVETIA T. A 2023/2024 - Simbolon, Rinci; H. Harahap, Siti Zahara; Damanik, Angela yosi (Universitas Quality, 2024)
The research aims to determine the effect of TTS (crossword puzzle) learning media on students' learning motivation at SDN 105273 helvetia. This quantitative study involves the entire fifth-grade student population at SD helvetia. The research results are targeted for publication in an accredited national journal. The study was conducted at SDN 105273 Helvetia, involving an experimental class using TTS and a control class without TTS. The research findings indicate an increase in students' learning motivation when using TTS, with the hypothesis test confirming its significant influence. In conclusion, the TTS learning media has a significant positive effect on the learning motivation of fifth-grade students at SDN 105273 helvetia, resulting in a statistically significant increase in learning motivation compared to students not using TTS.